GE_GERICHTE C/25954/2013 vom 20. Juni 2014 - GE Cour de justice (2014)
RAISON DE COMMERCE; PROTECTION DES MARQUES; VIOLATION DU DROIT À LA MARQUE(DROIT CIVIL); RISQUE DE CONFUSION | CO.951.2; CO.956.1; LPM.13; LPM.3